The last of the Mohicans - McRae, John, 1926-; Green, Harry; Maloney, David; Ives, Kenneth; Madoc, Philip; Abineri, John; Warwick, Richard, 1945-1997; Crawford, Andrew; Goodman, Tim; Davis, Joanna; Maynard, Patricia; Cooper, James Fenimore, 1789-1851.; et al. (Port Washington, NY : KOCH Vision : Distributed by KOCH Entertainment, 2007)
In 1757, during the French and Indian War, half-sisters Cora and Alice Munro set out to join their father, the British Commander of Fort William Henry. After they are betrayed by Magua, the sisters are rescued by Hawkeye whose efforts to lead them to safety are aided by the noble Mohican Uncas, the last of this tribe
Based on the novel by James Fenimore Cooper
Originally broadcast on BBC's Masterpiece theatre in 1971
Title from container
Cinematographer, Ken Westbury ; editor, Roger Crittenden ; music, Dudley Simpson
Kenneth Ives, Philip Madoc, John Abineri, Richard Warwick, Andrew Crawford, Tim Goodman, Joanna Davis, Patricia Maynard
Keywords: Cooper, James Fenimore, -- 1789-1851 -- Film and video adaptations; Bumppo, Natty (Fictitious character) -- Drama; Mohegan Indians -- Drama; Frontier and pioneer life -- Drama; Foreign television programs -- England; United States -- History -- French and Indian War, 1755-1763 -- Drama; Television mini-series; Historical television programs; Adventure television programs; War television programs; Television adaptations